The effectiveness of and satisfaction with high-fidelity simulation to teach cardiac surgical resuscitation skills to nurses - McRae, Marion E.; Chan, Alice; Hulett, Renee; Lee, Ai Jin; Coleman, Bernice (Intensive & critical care nursing, 2017)
•Simulation increased self-confidence to perform cardiac surgical resuscitation procedures.•Self-confidence was not correlated with performance time of cardiac surgical resuscitation.•Nurses were highly satisfied with the simulation.•Research is needed to study the impact of simulation on patient outcomes. There are few reports of the effectiveness or satisfaction with simulation to learn cardiac surgical resuscitation skills. To test the effect of simulation on the self-confidence of nurses to perform cardiac surgical resuscitation simulation and nurses’ satisfaction with the simulation experience. A convenience sample of sixty nurses rated their self-confidence to perform cardiac surgical resuscitation skills before and after two simulations. Simulation performance was assessed. Subjects completed the Satisfaction with Simulation Experience scale and demographics. Self-confidence scores to perform all cardiac surgical skills as measured by paired t-tests were significantly increased after the simulation (d=−0.50 to 1.78). Self-confidence and cardiac surgical work experience were not correlated with time to performance. Total satisfaction scores were high (mean 80.2, SD 1.06) indicating satisfaction with the simulation. There was no correlation of the satisfaction scores with cardiac surgical work experience (τ=−0.05, ns). Self-confidence scores to perform cardiac surgical resuscitation procedures were higher after the simulation. Nurses were highly satisfied with the simulation experience.